Pengelolaan Keuangan Keluarga pada Dharma Wanita SMK N 1 Alian Kebumen: Peningkatan Kemandirian Ekonomi melalui Pelatihan Keuangan - Suci Wahyuni, Reni (LP3M Universitas Putra Bangsa, 2025)
This community service activity aims to improve understanding of family financial management for members of Dharma Wanita SMK N 1 Alian Kebumen. This training educates participants about the importance of efficient financial management, teaches basic techniques in planning household finances, and provides insight into investment and savings. This activity involved 30 Dharma Wanita members who were very enthusiastic in participating in the training. The results of this training showed an increase in participants' knowledge in terms of family financial planning that can be applied in everyday life. This training is expected to improve the economic welfare of the families of Dharma Wanita members of SMK N 1 Alian Kebumen